The role of warnings in regulation: Keeping control with less punishment - Karine Nyborg; Kjetil Telle (University of Oslo, Department of Economics, 2003)
Regulatory agencies frequently present violators with warnings, not pursuing prosecution if the violation ceases upon receipt of the warning. We show how such warnings may help regulators to keep control: Prosecution is costly for the regulator, and insu.cient prosecution e.orts yield low penalties. Thus, with a limited regulatory budget, threats of harsh sanctions are credible only if the number of violators is low. This produces multiple Nash equilibria. If firms may make mistakes, the economy can accidentally switch from one equilibrium to another. Warnings reduce substantially the probability of such accidental switches from the high to the low compliance equilibrium.
Keywords: D62; K42; L51; Q28; 330; Enforcement; warnings; multiple equilibria; Dynamisches Gleichgewicht; Normbefolgung; Öffentliches Gut; Theorie; Rechtsdurchsetzung